Provider Adherence to Syphilis Testing Recommendations for Women Delivering a Stillbirth - Patel, Chirag G. (Sex Transm Dis, 2017)
OBJECTIVE: To assess overall adherence to Centers for Disease Control and Prevention and American College of Obstetrics and Gynecology recommended guidelines for syphilis testing among women who delivered a stillbirth and compare it with other tests recommended for stillbirth evaluation. METHODS: We used MarketScan claims data with 40 million commercially insured and 8 million Medicaid enrollees annually to estimate prenatal care and follow-up testing among women who had stillbirths between January 1, 2013, and December 24, 2013. Stillbirth was identified if women had any International Classification of Disease, Ninth Revision codes related to a stillbirth outcome. Among women with stillbirths, we estimated the proportions of women who received prenatal care and prenatal syphilis testing within 280 days before stillbirth, and testing at the time of stillbirth (syphilis testing, complete blood count, placental examination and autopsy) using Physician’s Current Procedural Terminology codes. RESULTS: We identified 3672 Medicaid-insured women and 6023 commercially insured women with stillbirths in 2013. Approximately, 61.7% of Medicaid-insured women and 66.0% of commercially insured women had claims data indicating prenatal syphilis testing. At the time of stillbirth, Medicaid-insured and commercially insured women had similar rates of syphilis testing (6.5% vs 9.3%), placental examination (61.6% vs 57.8%), and complete blood count (31.9% vs 37.6%). Autopsies were too infrequent to be reported. Approximately, 34.6% of Medicaid-insured women and 29.7% of commercially insured women had no syphilis testing either prenatally or at the time of stillbirth. CONCLUSIONS: Syphilis testing among women after stillbirth was less than 10%, illustrating limited adherence to Centers for Disease Control and Prevention and American College of Obstetrics and Gynecology recommendations. Such low prenatal and delivery syphilis testing rates may impact the number of stillbirth cases identified as congenital syphilis cases and reported to the national surveillance system. Our results emphasize the need to improve syphilis testing to improve diagnosis of syphilitic stillbirths, identify women with syphilis infection, and provide treatment to these women to avoid syphilis-related adverse outcomes.